**1. Divide the polynomial p(x) by the polynomial g(x) and find the quotient and remainder in each of the following: **

**(i) p(x) = x ^{3} – 3x^{2} + 5x – 3 ; g(x) = x^{2} – 2**

**(ii) p(x) = x ^{4} – 3x^{2} + 4x + 5 ; g(x) = x^{2} + 1 – x**

**(iii) p(x) = x ^{4} – 5x + 6; g(x) = 2 – x^{2}**

Solution:

(i)p(x) = x^{3} – 3x^{2} + 5x – 3 ; g(x) = x^{2} – 2

Quotient = x − 3

Remainder = 7x − 9

(ii)p(x) = x^{4} – 3x^{2} + 4x + 5 ; g(x) = x^{2} + 1 – x

Quotient = x^{2} + x − 3

Remainder = 8

(iii) p(x) = x^{4} – 5x + 6; g(x) = 2 – x^{2}

Quotient = −x^{2} − 2

Remainder = −5x +10

2. **Check whether the first polynomial is a factor of the second polynomial by dividing the second polynomial by the first polynomial:**

**(i) t ^{2} – 3, 2t^{4} – 2t^{2} – 9t – 12**

**(ii) x ^{2} + 3x + 1, 3x^{4} + 5x^{3} – 7x^{2} + 2x + 2**

**(iii) x ^{3} – 3x + 1, x^{5} – 4x^{3} + x^{2} + 3x + 1**

Solution:

(i) t^{2} – 3, 2t^{4} – 2t^{2} – 9t – 12

t^{2} – 3 = t^{2 }+ 0.t – 3

Since the remainder is 0,

Hence, t^{2} – 3 is a factor of 2t^{4} + 3t^{3} – 2t^{2} – 9t – 12

(ii) x^{2} + 3x + 1, 3x^{4} + 5x^{3} – 7x^{2} + 2x + 2

Since the remainder is 0,

Hence x^{2} + 3x + 1 is a factor of 3x^{4} + 5x^{3} -7x^{2} + 2x + 2

(iii) x^{3} – 3x + 1, x^{5} – 4x^{3} + x^{2} + 3x + 1

Since the remainder ≠ 0

Hence x^{3} – 3x + 1 is not a factor of x^{5 }– 4x^{3} + x^{2} + 3x + 1

**3. ****Obtain all other zeroes of 3x ^{4 }+ 6x^{3} – 2x^{2} – 10x -5, if two of its zeroes are √(^{5}/_{3}) and -√(^{5}/_{3})**

Solution:

p(x) = 3x^{4 }+ 6x^{3} – 2x^{2} – 10x -5

Since the two zeros are √(^{5}/_{3}) and -√(^{5}/_{3})

Therefore, [x – √(^{5}/_{3})][x + √(^{5}/_{3})] = (x^{2} – ^{5}/_{3}) is a factor of 3x^{4 }+ 6x^{3} – 2x^{2} – 10x -5. Thus

we divide the given polynomial by x^{2} – ^{5}/_{3}

3x^{4 }+ 6x^{3} – 2x^{2} – 10x -5 = (x^{2} – ^{5}/_{3})(3x^{2} + 6x + 3)

= 3(x^{2} – ^{5}/_{3})(x^{2} + 2x + 1)

We factorise x^{2} + 2x + 1 = (x + 1 )^{2}

Therefore, its zero is given by x + 1 = 0 or x = −1

As it has the term (x+1)^{2} , therefore, there will be 2 zeroes at x = −1. Hence, the zeroes of the given polynomial are √(^{5}/_{3}) , – √(^{5}/_{3}), -1 and -1.

**4. ****On dividing x ^{3} – 3x^{2} + x + 2 by a polynomial g(x), the quotient and remainder were x − 2 and − 2x + 4, respectively. Find g(x).**

Solution:

p(x) = x^{3} – 3x^{2} + x + 2 [dividend]

Quotient = (x -2)

Remainder = (-2x + 4)

Divisor = g(x)

Dividend = Divisor × Quotient + Remainder

x^{3} – 3x^{2} + x + 2 = g(x) x (x -2) + (-2x + 4)

x^{3} – 3x^{2} + x + 2 + 2x – 4 = g(x).(x – 2)

g(x) = [x^{3} – 3x^{2} + 3x – 2]/[x-2]

g(x) = x^{2} – x + 1

**5. Give examples of polynomial p(x), g(x), q(x) and r(x), which satisfy the division algorithm and **

**(i) deg p(x) = deg q(x) **

**(ii) deg q(x) = deg r(x)**

**(iii)deg r(x) = 0 **

Solution:

According to the division algorithm, if p(x) and g(x) are two polynomials with g(x) ≠ 0,

then we can find polynomials q(x) and r(x)

such that p(x) = g(x) × q(x) + r(x), where r(x) = 0 or degree of r(x) < degree of g(x)

Degree of a polynomial is the highest power of the variable in the polynomial.

(i) deg p(x) = deg q(x)

Degree of quotient will be equal to degree of dividend when divisor is constant ( i.e., when any polynomial is divided by a constant). Let us assume the division of 6x^{2} + 2x + 2 by 2.

Here, p(x) = 6x^{2} + 2x + 2

g(x) = 2 q(x) = 3x^{2} + x + 1 and r(x) = 0

Degree of p(x) and q(x) is the same i.e., 2.

Checking for division algorithm, p(x) = g(x) × q(x) + r(x)

6x^{2} + 2x + 2 = (2)* (3×2 + x + 1) + 0

Thus, the division algorithm is satisfied.

(ii) deg q(x) = deg r(x)

Let us assume the division of x^{3} + x by x^{2} ,

Here, p(x) = x^{3} + x g(x) = x^{2}

q(x) = x and r(x) = x

Clearly, the degree of q(x) and r(x) is the same i.e., 1.

Checking for division algorithm, p(x) = g(x) × q(x) + r(x)

x^{3} + x = (x^{2} ) × x + x

x^{3} + x = x^{3} + x

Thus, the division algorithm is satisfied.

(iii)deg r(x) = 0

Degree of remainder will be 0 when remainder comes to a constant.

Let us assume the division of x^{3} + 1 by x^{2} .

Here, p(x) = x^{3} + 1

g(x) = x_{2}

q(x) = x and r(x) = 1

Clearly, the degree of r(x) is 0.

Checking for division algorithm, p(x) = g(x) × q(x) + r(x) x 3 + 1 = (x^{2} ) × x + 1 x 3 + 1 = x^{3 }+ 1

Thus, the division algorithm is satisfied.

Do you do physics too

Haha currently we are not working on physics baby. By the by in which class you are studying?

If you need physics we can re-direct you to physics sites…

I don’t mind if you can do so

Sure. We will get back to you soon 🙂

Thanks!

You are always welcome

For physics follow this site .. i felt it very interesting and found clear explanation with proper images //sarneetphysics.wordpress.com/